1992
DOI: 10.2118/22836-pa
|View full text |Cite
|
Sign up to set email alerts
|

Results of Stress-Oriented and Aligned Perforating in Fracturing Deviated Wells

Abstract: Summary This paper reports the first results of stress-oriented and aligned perforating of deviated wells at the Kuparuk River field, Alaska. Preferred perforation alignment and Preferred perforation alignment and spacing are calculated for each well so the fractures from individual perforations link to produce a single perforations link to produce a single "zipper" fracture plane along the deviated wellbore. Results of the first application of this technique are presented from the 26-well de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…The experimental observation is in general consistent with the analytical results presented in this section. The method of oriented perforation and high pressure fracturing have been applied to the field by Handren et al [12], Pearson et al [13], and Couet et al [14]. These authors have confirmed the prediction from this method.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The experimental observation is in general consistent with the analytical results presented in this section. The method of oriented perforation and high pressure fracturing have been applied to the field by Handren et al [12], Pearson et al [13], and Couet et al [14]. These authors have confirmed the prediction from this method.…”
Section: Resultsmentioning
confidence: 76%
“…Equation (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) can then be rearranged in terms of the dislocation density parameter A n as follows:…”
Section: Solution Methodsmentioning
confidence: 99%
“…Several authors (see Refs. 7,[18][19][20][21] have shown that perforations, to be effective for fracture initiation, should be in phase with the anticipated fracture direction, i.e., the fracture length is along the maximum orthogonal stress and the fracture plane is perpendicular to the minimum orthogonal stress. Design of a successful perforation program is beyond the scope of this study.…”
Section: Fracture Initiation Criteriamentioning
confidence: 99%
“…According to laboratory experiments (Pearson et al, 1992;Zhu et al, 2014;Van de Ketterij and de Pater, 1997), theoretical studies and field applications (Fallahzadeh et al, 2010a(Fallahzadeh et al, , 2010b, it could be concluded that the near-wellbore effects of hydraulic fracturing are much more complicated in highly deviated wellbores. For example, if there is a perforation phase error the microannulus usually generates easily at the interface of formation and cement sheath.…”
Section: Introductionmentioning
confidence: 99%